DETERMINAN NET INTEREST MARGIN PERBANKAN DI INDONESIA (STUDI KASUS: BANK BRI) - Sinaga, Vita Marceline; Wahyudi, Setyo Tri (Contemporary Studies in Economic, Finance and Banking, 2023)
The development of banking Net Interest Margin (NIM) in Indonesia shows a high value among other ASEAN countries. A high NIM ratio value does not indicate that the bank's condition is good. Bank Indonesia has a NIM target with a value range of 3% -4%. However, in reality, in the case of state-owned banks, no one has been able to achieve Bank Indonesia's target. The influence of bank internal and external factors has a significant contribution to the value of NIM. This study aims to analyze the determinants of the net interest margin of Indonesian banking by using a case study of Bank BRI. This research is a quantitative research with secondary data sources derived from the company's financial statements. The analytical method used is the two stage least square (TSLS). The results showed that the variables NPL, LDR, CAR, and deposits had a significant effect on NIM. Meanwhile, BOPO and SBK have no significant effect on NIM.